直齿锥齿轮齿廓圆弧修形 - 陈霞; 夏巨谌; 胡国安; 金俊松; 李大才; 胡明发 (Jixie Chuandong, 2007)
In order to minimize the fluctuation of gear transmission error and combined torsional mesh stiffness, tooth profile modification with circular curve was developed for involute bevel gears. At the same time it must ensure the variation of the load appear smooth transition. A static calculation of a transmission system of bevel gears with tooth profile modifications was given. It indicates the tooth relieved engaging gears have ideal effect on reducing vibration.